Organizational Immunity and its Role in Institutional Excellence: An Exploratory Study from Employees’ Perspectives at the Oil Products Distribution Company / Ministry of Oil - Huda Qasim Saeed , Huda Qasim Saeed (Journal of Economics and Administrative Sciences, 2025)
This research study investigates the impact of organizational immunity on the attainment of institutional excellence at the Oil Products Distribution Company of the Iraqi Ministry of Oil. The components that encapsulate organizational immunity include but are not limited to organizational learning, organizational memory, and organizational DNA, which together empower the organization for adaptive response in the face of challenges and the resilience to bounce back. From here, an institution is expected to demonstrate excellence in leadership, in human resources, in service quality, and in organizational culture. The study further states that there is a positive significant relationship between the tenets of organizational immunity and institutional excellence. Thus, enhanced institutional immunity creates institutional resilience, which enables taking care of stability, adaptability to the environment, and sustainable competitive advantage. Results show that organization learning and memory contribute significantly to institutional excellence in building the retention and adaptability of knowledge in the pro-active response to challenges. The study, therefore, emphasizes the need for improving organizational learning through continuous development programs and using organizational memory to ensure consistency within decision-making and operational success. It also underscores the importance of culture-building on resilience and adaptability toward creating institutional excellence sustainable over time and positioning the organization for competitive advantage and growth.